1997
DOI: 10.1089/tmj.1.1997.3.159
|View full text |Cite
|
Sign up to set email alerts
|

Public Knowledge, Perception, and Expressed Choice of Telemedicine in Rural West Virginia

Abstract: More work needs to be done to demonstrate the efficacy of telemedicine and disseminate this knowledge to the public.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 0 publications
4
23
0
Order By: Relevance
“…As reported by Brick et al 1 , higher socio-economic status (insofar as this was recorded in the present study by the item 'Works outside the home' and education see Table 3) was associated with greater willingness to use telemedicine for routine care. This might be related to the greater access that people of this type have to sources of communication such as periodicals, professional journals, television and the Internet.…”
Section: Discussionsupporting
confidence: 83%
“…As reported by Brick et al 1 , higher socio-economic status (insofar as this was recorded in the present study by the item 'Works outside the home' and education see Table 3) was associated with greater willingness to use telemedicine for routine care. This might be related to the greater access that people of this type have to sources of communication such as periodicals, professional journals, television and the Internet.…”
Section: Discussionsupporting
confidence: 83%
“…Although patient perceptions have been studied after telemedicine consultations to assess satisfaction with the technology as a means of providing care (Allen & Hayes, 1995;Mekhjian, Turner, Gailiun, & McCain, 1999), only a few studies have investigated preexperience perceptions, perceptions that shape patients' initial willingness to give telemedicine a try. This small number of studies includes Bashshur (1978) and Brick, Bashshur, Brick, and D'Alessandri (1997). Both of these investigations found that patients do not perceive telemedicine as preferable to seeing a doctor in person, although patients do seem to appreciate the potential applications of telemedicine for minor problems or for emergency situations.…”
Section: Telemedicinementioning
confidence: 99%
“…There is scant research on viewpoints about telemedicine among the target population before the introduction of telemedicine. Some exceptions include studies by Bashshur [22], Brick et al [23], and Turner et al [21]. The first two studies found that patients do not perceive telemedicine as preferable to seeing a doctor in person, even though they appreciated the usefulness of telemedicine for emergency situations and minor problems.…”
Section: Introductionmentioning
confidence: 99%